Building social capital among rural, older Australians through information and communication technologies: A review article. (11th October 2012) - Warburton, Jeni; Cowan, Sue; Bathgate, Tenzin
<x xml:space="preserve">Abstract</x> This paper undertakes a comprehensive review of the growing international literature on the adoption and use of information and communication technologies (ICTs) among older people. Issues associated with access and adoption of ICTs among older people living in rural communities will be explored, drawing on social capital as a theoretical lens through which to identify how these new technologies can build healthy ageing. ICTs as bridging social capital can address some of the challenges of service provision in rural Australia and provide access to more extensive information and resources. ICTs can also contribute to bonding social capital through access to other forms of communication to build on local connectedness. However, rural, older people face particular challenges of access, which may exacerbate the cycle of rural social exclusion. In the context of the Australian National Broadband rollout, it is timely to consider how some of these disparities can be addressed.